Study of the Effect of Synthesis Conditions on the Structural Properties of Biomimetic Polysaccharide-Templated Mesoporous Silica - Nataliya Zatonskaya; Sergey Karpov (Proceedings)
In our work, we chose chitosan (polysaccharide) as a template for the synthesis of mesoporous silica-based material (ZChM) [...]